RANCANG BANGUN SISTEM INFORMASI PMR WIRA SMK BATIK 1 SURAKARTA BERBASIS WEBSITE MENGGUNAKAN FRAMEWORK CODEIGNITER - Oktavia Astri (JIMSTEK: Jurnal Ilmiah Sains dan Teknologi, 2020)
SMK (Vocational Senior High School) Batik 1 Surakarta has an extracurricular organization PMR Wira SMK Batik 1 Surakarta. PMR has activities such as registeringnew members to increase the number of members. PMR encountered problems with the registration process manually by filling out the registration form. Therefore, it is necessary to build a website-based of PMR Wira SMK Batik 1 Surakarta information system using the CodeIgniter framework. It aims to assist members in the member registration process and to help users get information about the PMR organization as needed. Data collection techniques used observation, interviews and documentation and questionnaires. Furthermore, this study used a system development method of waterfall method which consist of six stages, namely system analyst and design, software requirements analys, system design, coding, testing and system maintenance. This application was build with the CodeIgniter framework, PHP programming language and Mysql database. The result of testing the system using the webqual method show that the quality of usability has a negative effect on user satisfaction because it has a significance of 0.610 > 0.05, while information quality has a negative effect on user satisfaction since it has a significance value of 0.204 > 0.05. Moreover, the quality of service interactions has a positiveeffect on satisfaction users since it has a significance of 0.007 < 0.05.Quality of usability, information quality and service quality of interaction simultaneously affect user satisfaction because it has a significance of 0.000 < 0.05. Therefore, it can be concluded that the user feels satisfied with the system created.